The effectiveness of Pilates exercises on treating low back pain - Mikołajczyk, Edyta; Żegleń, Kinga (Health Promotion & Physical Activity, 2019)
Introduction: Back pain is now a common problem. The study aimed to examine the effectiveness of Pilates exercises on the subjective spinal pain discomfort, degree of quality-of-life impairment and the lower back mobility. Material and methods: It was conducted in a group of 30 participants with chronic low back pain in whom, before and after the twelve-week Pilates exercise interventions, the level of subjective pain tolerance (VAS scale), lumbar spine mobility and the degree of quality-of-life impairment were assessed. Results: Involvement in the Pilates exercise programme helped to reduce subjective pain complaints, improved the spinal range of motion in all planes and enhanced the quality of life in all participants. Conclusions: The Pilates method is an effective tool in treating chronic low back pain.